Leveraging 3D Technology for Students with Autism: An innovative university-community collaboration for skill development and vocational exploration - Cheryl A Wright; Scott D Wright; Marissa L Diener; Deborah Rafferty; Allison Sampson (Gateways, 2017)
This article describes a university-community collaboration in which an inter-professional team partnered to provide students with autism spectrum disorder (ASD) a paid job opportunity to apply 3D modelling skills for a local construction company. Providing meaningful vocational opportunities to improve the transition to adulthood for individuals with ASD is imperative, as individuals with ASD have unemployment rates that are some of the highest of all disabilities. This novel evidence-supported educational program was designed to develop 3D technology skills, explore vocational careers and promote social engagement through shared interests for transition-age youth with ASD. Both parents and students reported many successful outcomes, including increase in student self-confidence, social and technology skill development and the opportunity for vocational exploration by these young people. Implications of the case study are reported in relation to university-community partnerships and the critical role of community collaboration in addressing the high rates of unemployment in individuals with autism.